Case report: Combination therapy for hepatocellular carcinoma with inferior vena cava or right atrial tumor thrombus in the era of combined targeted and immunotherapeutic agents - Hai, Yubin; Lin, Tingting; Wang, Guangyi; Sun, Xiaodong; Wang, Lan; Hai, Yuying; Chen, Saisai; Shi, Xiaoju (Frontiers in Oncology, 2024)
Primary liver cancer, predominantly hepatocellular carcinoma (HCC), is a leading cause of cancer-related mortality. Tumor thrombus (TT) in the inferior vena cava (IVC) or right atrium (RA) significantly worsens prognosis. We present four cases of male patients (average age 57) with HCC and TT extending into the IVC/RA, treated at our center. All underwent hepatectomy and TT resection, with targeted therapy (lenvatinib) and immunotherapy (sintilimab) administered post-operatively. Case 1 involved a 59-year-old male who had a right hepatectomy and TT resection in the IVC, followed by targeted therapy and immunotherapy, and is currently alive 74 months post-treatment. Case 2, a 48-year-old male, had a right hepatic lobectomy and TT resection in the IVC/RA, followed by liver transplantation 54 months postoperatively, with no recurrence. Case 3, a 66-year-old male, underwent a left hepatectomy and TT resection in the IVC, remaining disease-free 27 months postoperatively. Case 4, a 55-year-old male, received 15 cycles of combined targeted and immune therapy, followed by left hepatectomy and TT resection in the IVC/RA, with no recurrence 22 months postoperatively. Surgical resection combined with targeted and immunotherapy may enhance survival in advanced HCC patients with TT in the IVC/RA. Further studies are required to corroborate these findings.